2009
DOI: 10.1109/icde.2009.119
|View full text |Cite
|
Sign up to set email alerts
|

Top-k Exploration of Query Candidates for Efficient Keyword Search on Graph-Shaped (RDF) Data

Abstract: Keyword queries enjoy widespread usage as they represent an intuitive way of specifying information needs. Recently, answering keyword queries on graph-structured data has emerged as an important research topic. The prevalent approaches build on dedicated indexing techniques as well as search algorithms aiming at finding substructures that connect the data elements matching the keywords. In this paper, we introduce a novel keyword search paradigm for graph-structured data, focusing in particular on the RDF dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
267
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(268 citation statements)
references
References 19 publications
0
267
0
1
Order By: Relevance
“…Therefore, we rely on a top-k procedure to generate candidate interpretations and obtain the possible results that best match the user information need. We build on our previous work [17] on translating keyword queries into structured queries based on a graph-exploration technique. For this purpose, we consider available knowledge bases and data as data graphs as defined previously.…”
Section: Keyword Query Interpretation and Structured Query Generationmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we rely on a top-k procedure to generate candidate interpretations and obtain the possible results that best match the user information need. We build on our previous work [17] on translating keyword queries into structured queries based on a graph-exploration technique. For this purpose, we consider available knowledge bases and data as data graphs as defined previously.…”
Section: Keyword Query Interpretation and Structured Query Generationmentioning
confidence: 99%
“…It has been shown that keyword search is most efficient when the exploration for possible interpretations is performed on an augmented schema graph, instead of using the entire data graph (c.f. [17]). The schema graph can be trivially obtained from the class and property definitions in the data, or might be pre-given as an ontology.…”
Section: Keyword-to-element Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent approach BLINKS [12], based on [13], selects clusters according to the smallest cardinality. Thanh et al [23] presented a search algorithm for RDF-Graphs based on one iterator per surrogate set. Recently, Kasneci et al [12] proposed an approximation algorithm for Steiner trees that allows for a fast retrieval of relationship graphs based on minimal weights.…”
Section: Related Workmentioning
confidence: 99%